Analysis of Cytokine Levers in Pleural Effusions of Tuberculous Pleurisy and Tuberculous Empyema - Lei Yang; Yan-Jie Hu; Fu-Gen Li; Xiu-Jun Chang; Tian-Hui Zhang; Zi-Tong Wang (Hindawi Limited, 2016)
The aim is to examine whether the interleukin-1β (IL-1β), IL-2, IL-6, tumor necrosis factor-α (TNF-α), plasminogen activator inhibitor type-1 (PAI-1), and tissue plasminogen activator (t-PA) levels were different in pleural effusions of tuberculous pleurisy and tuberculous empyema. IL-1β, IL-2, IL-6, TNF-α, PAI-1, and t-PA levels in pleural fluids of 40 patients with tuberculous pleurisy and 38 patients with tuberculous empyema were measured. The levels of IL-1β, PAI-1, and t-PA in the pleural effusions were different between tuberculous pleurisy and tuberculous empyema; it could be helpful to differentiate the two diseases. The levels of PAI-1, IL-1β were higher and t-PA, IL-6 were lower in pleural effusions of the patients with tuberculous empyema and who must undergo operation than the patients who could be treated with closed drainage and anti-TB chemotheraphy. These indications may be helpful to evaluate whether the patient needs the operation.